ORAL TREATMENT WITH NICORANDIL AT DISCHARGE IS ASSOCIATED WITH REDUCED MORTALITY AFTER ACUTE MYOCARDIAL INFARCTION - Y. Sakata; D. Nakatani; M. Shimizu; Sh. Suna; M. Usami; S. Matsumoto; M. Hara; S. Sumitsuji; Sh. Kawano; K. Iwakura; T. Hamasaki; H. Sato; et al. (Российский кардиологический журнал)
Background. Previous studies showed that nicorandil can reduce coronary events in patients with coronary artery disease. However, it is unclear whether oral nicorandil treatment may reduce mortality following acute myocardial infarction (AMI). Methods and Results. We examined the impact of oral nicorandil treatment on cardiovascular events in 1846 AMI patients who were hospitalized within 24 h after AMI onset, treated with emergency percutaneous coronary intervention (PCI), and discharged alive. Patients were divided into those with (Group N, n = 535) and without (Group C, n = 1311) oral nicorandil treatment at discharge. No significant differences in age, gender, body mass index, prevalence of coronary risk factors, or history of myocardial infarction existed between the two groups; however, higher incidences of multi-vessel disease, and a lower rate of successful PCI were observed in Group N. During the median follow-up of 709 (340–1088) days, allcause mortality rate was 43% lower in Group N compared with Group C (2.4% vs. 4.2%, stratified log-rank test: p = 0.0358). Multivariate Cox regression analysis revealed that nicorandil treatment was associated with all-cause death after discharge (Hazard ratio 0.495, 95% CI: 0.254–0.966, p = 0.0393), but not for other cardiovascular events such as re-infarction, admission for heart failure, stroke and arrhythmia. Conclusions. The results suggest that oral administration of nicorandil is associated with reduced incidence of death in the setting of secondary prevention after AMI.